Nanoplating of a SnO2 thin-film on MXene-based sponge for stable and efficient solar energy conversion. Issue 16 (16th April 2020) - Zhang, Qi; Fu, Ze; Yu, Hongtao; Chen, Shuo
Abstract : An effective strategy to stabilize an MXene-based sponge by nanoplating with a SnO2 thin-film reveals stable solar-driven generation of clean-water and electricity. Abstract : The poor oxygen resistance of MXene-based materials greatly limits their large-scale applications in solar-energy storage and conversion. Herein, we report a MXene-based sponge nanoplated with a SnO2 thin-film (SnO2 -SPM) for stable solar-driven simultaneous water purification and electricity generation. This SnO2 thin-film nanoplating strategy prevents the surface oxidation of the MXenes by isolating them from O2, thus ensuring their highly-efficient and long-term light-to-heat conversion. A stable water output (1.41 kg m −2 h −1, reused 30 d) with a thermal efficiency of approximately 84.8% was achieved under 1-sun in various wastewaters ( e.g., saline waters, strong acid, alkali solutions and heavy metal wastewaters), highlighting the corrosion resistance and antifouling functionality. Steady power generation (∼3.6 V) for 100 h during water purification further demonstrates the reliability of this strategy. The COMSOL simulation helps us to understand how different thicknesses of the SnO2 thin-film influence the surface-temperature distribution of SnO2 -SPM. This work lays the foundation for the application of MXenes in long-term electricity and clean-water production.